“Cara inchada” (periodontal disease) in calves kept on Panicum maximum pastures - Döbereiner, Jürgen; Rosa, Ivan Valadão; Lazzari, Ademir A. (Pesquisa Agropecuaria Brasileira, 2014)
Six, 4 to 5 months old calves affected by periodontal lesions were kept on a Guinea grass (Panicum maximum Jacq.) pasture cleared of weeds for 5 months. Another group of eight of about 1 year old calves and also affected by "cara inchada" were kept grazing on such a clean pasture for 7 months. The experiments were conducted on two farms where the disease has been observed to be present, in the region of Rondonópolis, Mato Grosso. When the animals were reexamined two or three times within 2 to 6 months, it was found that the periodontal lesions had persisted or worsened in almost all of them. A number of 67 cows were introduced onto the clean P. maximum pasture of one of the two forms together with their 3 week old calves. Up until the calves reached the age of 9 months, periodontal lesions had been found in 52.2% of them. It was concluded by these experiments that the alimentary factor responsible for "cara inchada" seems to be present in the P. maximum pastures of farms where the periodontal disease occurs.